Thyroid function, the risk of dementia and neuropathologic changes: The Honolulu-Asia Aging Study - de Jong, Frank Jan (2007)
Thyroid dysfunction is associated with cognitive impairment and dementia, including Alzheimer disease (AD). It remains unclear whether thyroid dysfunction results from, or contributes to, Alzheimer pathology. We determined whether thyroid function is associated with dementia, specifically AD, and Alzheimer-type neuropathology in a prospective population-based cohort of Japanese-American men. Thyrotropin, total and free thyroxine were available in 665 men aged 71–93 years and dementia-free at baseline (1991), including 143 men who participated in an autopsy sub-study. During a mean follow-up of 4.7 (SD: 1.8) years, 106 men developed dementia of whom 74 had AD. Higher total and free thyroxine levels were associated with an increased risk of dementia and AD (age and sex adjusted hazard ratio (95% confidence interval) per SD increase in free thyroxine: 1.21 (1.04; 1.40) and 1.31 (1.14; 1.51) respectively). In the autopsied sub-sample, higher total thyroxine was associated with higher number of neocortical neuritic plaques and neurofibrillary tangles. No associations were found for thyrotropin. Our findings suggest that higher thyroxine levels are present with Alzheimer clinical disease and neuropathology.